Orientasi Pengelolaan Kelas - Sri Akidah; Muhammad Satir (MISOOL: Jurnal Pendidikan Dasar, 2022)
The teacher is one of the important factors in determining the success of the teaching and learning process in the classroom. Therefore, teachers are required to improve their role and competence. Competent teachers will be better able to create an effective learning environment and will be better able to manage their classes so that student learning outcomes are at an optimal level. Classroom management is a teacher's effort in creating good classroom environmental conditions with students acting according to their abilities, students can study in an orderly manner, student output is in accordance with the goals to be achieved with a social atmosphere that provides satisfaction, an atmosphere of discipline, intellectual development, emotional, attitude, and appreciation of students so that learning objectives are achieved effectively and efficiently. Classroom learning and management are two things that are carried out simultaneously in the learning process in class and have a very close relationship. Learning includes all activities carried out to achieve learning objectives, and classroom management includes activities that create and maintain optimal conditions for the learning process to occur.